CONSTRUCTIONS OF ELLIPSE DERIVED FROM SPACE - CHODOROVÁ, Marie; JUKLOVÁ, Lenka (Trends in education, 2016)
This article is devoted to the construction of an ellipse of given elements. Among the less known construction of the conic section include the structures derived from the space, mostly conic constructs are made through focus properties or based on collineation between circle and conic. Construction of ellipses in individual tasks are solved using a relationship derived from space. In all tasks we know the center of the ellipse and other elements - points and tangents of constructed ellipse. To constructions of ellipses there are used sections on an appropriately chosen rotating cylindrical surface which is displayed at the listed projection.
Keywords: ellipse; conjugate diameters of ellipse; section of the cilindrical surface.